Fascia: The tensional network of the human body (Churchill Livingstone Elsevier, 2012)
Compiled by experts of international renown, Fascia: The Tensional Network of the Human Body brings together very different contributors who share the desire to bridge the gap between theory and practice as much as possible in our current knowledge of the human fascia. With contributions from over 100 specialists and researchers from throughout the world, this new volume will be ideal for all professionals who have an interest in fascia and human movement - physiotherapists, osteopathic physicians and osteopaths, chiropractors, structural integration practitioners, manual therapists, massage therapists, acupuncturists, yoga or Pilates instructors, exercise scientists and personal trainers - as well as physicians involved with musculoskeletal medicine, pain management and rehabilitation, and basic scientists working in the field.